2016
DOI: 10.1002/ente.201500464
|View full text |Cite
|
Sign up to set email alerts
|

Shale Gas: A Review of the Economic, Environmental, and Social Sustainability

Abstract: The growth of the shale gas industry in the US has raised expectations that other nations could boost domestic gas production, leading to lower energy prices and improved energy security. However, the degree to which the US experience is transferable to other countries is uncertain. Furthermore, sustainability implications of shale gas development remain largely unknown. In an attempt to find out if and how shale gas could be exploited in a sustainable way, this paper reviews the economic, environmental, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(51 citation statements)
references
References 112 publications
(288 reference statements)
0
49
0
Order By: Relevance
“…The FEP database describes the identification and selection of the relevant elements for HF safety: characterization of the main geological features, definition of key events and understanding of main processes occurring during the exploration and exploitation of shale gas. Reviews on the risks and the risk assessment methodologies associated with HF can be found in e.g., Cooper et al (2016), Torres et al (2016), US EPA (2013); Vengosh et al (2014), Vidic et al (2013). The main objective of this work is to show the process of developing conceptual models for assessing the environmental impact of HF on groundwater aquifers based on a FEP database.…”
Section: Introductionmentioning
confidence: 99%
“…The FEP database describes the identification and selection of the relevant elements for HF safety: characterization of the main geological features, definition of key events and understanding of main processes occurring during the exploration and exploitation of shale gas. Reviews on the risks and the risk assessment methodologies associated with HF can be found in e.g., Cooper et al (2016), Torres et al (2016), US EPA (2013); Vengosh et al (2014), Vidic et al (2013). The main objective of this work is to show the process of developing conceptual models for assessing the environmental impact of HF on groundwater aquifers based on a FEP database.…”
Section: Introductionmentioning
confidence: 99%
“…The countries like Russia are yet uncertain to develop their shale gas and are unclear due to two reasons as (1) Russia may have large conventional energy resources to fulfil the energy demand or (2) the estimated unconventional resources are very limited to invest on their exploration and development (e.g. Cooper et al 2016).…”
Section: Shale Gas Reservoirs Characteristicsmentioning
confidence: 99%
“…Therefore, for such thin-rimmed formations with extremely low-permeability rock, it is recommended to Fig. 2 The illustration is the historical production status of US shale gas past, present and future from 1990 to 2040 Reproduced with permission from EIA 2013 (Cooper et al 2016) Fig. 3 Gas distributions in shale formation macro-scale to micro-scale.…”
Section: Shale Gas Reservoirs Hydraulic Fracturingmentioning
confidence: 99%
“…Novel, unfamiliar technologies usually raise safety concerns -CCS and hydraulic fracturing ('fracking') are just some of most recent examples where the general public have expressed their anxieties and worries about safety impacts of the new technologies (Shackley et al 2007;Cooper et al, 2016). In order to gain insight into potential safety concerns about CCU, the respondents were asked to indicate whether they would be worried about possible location of a CCU plant within their community.…”
Section: Safety Concernsmentioning
confidence: 99%